Examining the Effects of Higher Education Service Quality (HESQUAL) on Student Loyalty and Word-of-Mouth at an Indonesian Private University - Anisa Nur Litasari (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2024)
The purpose of this study is to investigate the elements that spur the growth of word-of-mouth and loyalty and to further explore the significance of perceived value and student happiness as motivators. This research methodology employs a quantitative approach and employs questionnaire-based surveys for data collection. The Islamic University of Indonesia's 295 active students enrolled in various study programs served as the study's samples. For this study, SPSS and PLS-SEM with SmartPLS software are used for data analysis. The results of this study show that perceived value, student loyalty, contentment, and word-of-mouth are all positively impacted by the quality of university services. These findings advance our knowledge of the process by which student behavior, such as loyalty and word of mouth is influenced by the quality of university services, as measured by satisfaction and perceived value.